A high-efficiency charge pump in BCD process for implantable medical devices *Project supported by the National Natural Science Foundation of China (No. 61474092). (October 2018) - Zhang, Jie; Zhang, Hong; Zhang, Ruizhi
Abstract: This paper presents a high-efficiency charge pump circuit composed of cascaded cross-coupled voltage doublers implemented in an isolated bipolar-CMOS-DMOS (BCD) technology for implantable medical devices. Taking advantage of the transistor structures in the isolated BCD process, the leakage currents caused by the parasitic PNP transistors in the cross-coupled PMOS serial switches are eliminated by simply connecting the inside substrate terminal to the isolation terminal of each PMOS transistor. The simple circuit structure leads to small parasitic capacitance in the voltage doubler, which in turn ensures high efficiency of the overall charge pump. The proposed charge pump with 5 cascaded voltage doublers is fabricated in a 0.35- μ m isolated BCD process. Measurement results with 2-V power supply, 1-MHz driving clock frequency and 40- μ A current load show that an efficiency of 72.6% is achieved, and the output voltage can be pumped to about 11.5 V at zero load current. The chip area of the charge pump is 1.6 × 0.35 mm 2 .